Pola komunikasi organisasi pustakawan-guru dalam pemberian layanan prima perpustakaan - Tine Silvana Rachmawati; Merryam Agustine (Perpustakaan Universitas Gadjah Mada, 2021)
Introduction. The purpose of this study is to examine the organizational communication patterns between librarians and teachers in providing quality library services. Data Collection Method. This is a qualitative research with a case study approach with librarians and teachers as samples. Data collection techniques were interviews, observations, and literature study. Data Analysis. Data analysis techniques were conducted by reducing data, presenting data, and then making conclusions or data verification. Results and Discussion. The results of this study indicate that a well-established organizational communication pattern between librarians and teachers consists of task coordination, problem-solving, information sharing, conflict resolution, and building togetherness or relationships. All of them supported excellent services. Conclusion. Librarian who implement a good horizontal organizational communication model can provide high-quality services to teachers who need information, which is beneficial to the library and the school as an organization. The recommendation of this study is that schools should be able to treat librarians as key people in organizing ideas and information resources, rather than as only as academic supporters.